Synaptotagmin: a multifunctional protein in the synaptic vesicle cycle - Loewen, Carin, author; Reist, Noreen, advisor; Rash, John, committee member; Handa, Robert, committee member; Betz, Bill, committee member (Colorado State University. Libraries, 2005)
Synaptotagmin is a synaptic vesicle protein whose cytosolic domain contains two C2 domains, C2A and C2B. In vitro, synaptotagmin interacts with numerous presynaptic proteins. Genetic studies have demonstrated that synaptotagmin is critical for full synaptic transmission, and implicate synaptotagmin in synaptic vesicle docking, Ca2+-sensing to trigger fusion and synaptic vesicle endocytosis. In vitro studies implicate synaptotagmin in synaptic vesicle priming. To further define synaptotagmin's role in the synaptic vesicle cycle, I examined three Drosophila synaptotagmin mutants at the third instar stage. The first was a synaptotagmin null (sytnull) mutant. The second harbored a mutation in the Ca2+-binding motif of synaptotagmin's C2B domain. The third harbored a mutation in the polylysine motif also located in the C2B domain. Although synaptic transmission is nearly abolished in sytnull mutants, the mutation does not cause gross morphological changes and synaptic arborizations develop normally. Indeed, with special care sytnull mutants can survive to adulthood. However, ultrastructural analysis revealed that synaptic vesicles, including docked vesicles, are severely decreased at active zones of sytnull neuromuscular junctions. sytnull terminals also accumulate large, membranous structures, possibly indicating a defect in endocytosis. These experiments permit sytnull third instars to serve as critical negative controls for synaptotagmin structure/function studies. Furthermore, they support a role for synaptotagmin in maintaining a population of synaptic vesicles in the nerve terminal, as well as in synaptic vesicle docking, Ca2+-sensing to trigger fusion, and synaptic vesicle endocytosis. Previous work has shown that synaptic transmission is more severely disrupted in C2B Ca2+-binding motif mutants than it is in sytnull mutants. However, unlike sytnull mutants, synaptic ultrastructure is normal in C2B Ca2+-binding motif mutants. These mutants show normal levels of synaptic vesicles, including docked vesicles, and no accumulation of large membranous structures. These results indicate that the C2B Ca2+-binding motif is not involved in synaptotagmin's role in maintaining a population of synaptic vesicles at nerve terminals, in synaptic vesicle docking or in endocytosis. Instead, the near elimination of synaptic transmission observed in these mutants is likely due to the protein's inability to bind Ca2+ by its C2B domain and undergo some critical Ca2+-dependent interaction, strongly supporting a role for synaptotagmin in Ca2+-sensing. Previous work has shown that the polylysine motif in synaptotagmin's C2B domain is also critical for full synaptic function. In vitro, this motif interacts with numerous presynaptic proteins. Thus, the defect in synaptic transmission recorded in C2B polylysine motif mutants, could be due to a disruption of any of these interactions. Here I present data implicating this motif in synaptic vesicle recycling. I demonstrate that the motif is not involved in synaptic vesicle endocytosis, but does play a role prior to vesicle fusion. Furthermore, the C2B polylysine motif mutants have a decreased probability of release. These results are consistent with the hypothesis that the polylysine motif is involved in synaptic vesicle priming. In summary, these studies demonstrate that synaptotagmin is a multifunctional protein in the synaptic vesicle cycle. Synaptotagmin plays an important role in synaptic vesicle docking, priming, Ca2+-sensing and endocytosis via distinct molecular interactions mediated by its various motifs.
Keywords: neurology; neurosciences